Pengaruh Tenure Audit dan Fee Audit terhadap Kualitas Audit dengan Kompetenesi sebagai Variabel Moderasi - Elga Juniar Naomi Soinia; Abriandi (UNIVERSITAS KALBIS, 2022)
This study aims to examine whether tenure audit and fee audit can influence audit quality with competence as moderator. This research used quantitative method through survey approach with questionnaires form which filled by 48 auditors in Central Jakarta from 6 Public Accounting Firm as respondents. The hypothesis in this study are tested using t test, F test, and interaction test (MRA). These results of this study indicate that tenure audit and fee audit partially or simultaneously can improve the quality of audit results. Furthermore, competence can’t moderate the influence of tenure audit on audit quality, but competence can strengthen the influence of fee audit on audit quality.